(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the life and scholarly legacy of Abū Bakr Muḥammad ibn ’Alī ibn Ismā’īl al-Qaffāl al-Shāshī (291/904–365/976), one of the most prominent Shāfi’ī jurists of the mediaeval Islamic world. Based on a comparative analysis of over twenty mediaeval biographical, historiographical, and geographical sources, the study reconstructs al-Qaffāl al-Shāshī’s biography, traces his intellectual journey from his native city Shāsh through the learning centres of Khurāsān, Iraq, Shām, and the Ḥijāz, and evaluates the scholarly debates surrounding his life. The article argues that a careful reading of the sources allows certain conclusions to be drawn with confidence, while other questions must remain open. Beyond its biographical contribution, the study situates al-Qaffāl al-Shāshī within the broader intellectual history of Transoxiana under the Samanids and considers his role in the consolidation of the Shāfi’ī school in the eastern Islamic world.